Identifikasi Faktor Internal dan Eksternal Melalui Strategi Pemasaran pada Usaha Kerajinan Salman Rotan di Kecamatan Lhoknga Kabupaten Aceh Besar - Marlina; Hanum, Filia; Safitri, Yuni Ayu; Fitriliana; Juwita; Mauliza, Putri; Amri, Saiful (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
This community service activity aims to look at internal and external factors through marketing strategies at Salman's rattan craft business, which is in the Lhoknga District area, Aceh Besar Regency and was initiated by Mr Salman starting in 1992. The methods used are the survey method and the sampling method, namely census method because there was only 1 respondent, namely Mr. Salman as the owner of a rattan craft business. The results of this activity show that there are internal and external factors through which the marketing strategy for the Salman rattan craft business has been implemented by Mr. Salman as the business owner, namely maintaining product sales prices to remain stable, expanding the product marketing network, ensuring the quality of goods/products of the rattan craft business , innovating rattan products and providing a more unique product appearance, providing training/counseling to employees carried out by business owners and collaborating with official authorities, as well as adding employees who have an interest in marketing